Micro-nano particle reinforced metal matrix composite material and preparation method thereof

By using molten salt medium and ultrasonic stirring technology in the preparation process of metal-based composite materials, the micro-nano particles are evenly distributed in the metal matrix, solving the problems of uneven dispersion, high cost and complex process, and realizing high-performance metal substrates Industrial production of composite materials.

CN119433259APending Publication Date: 2025-02-14MCC KUNYUAN (CHONGQING) METAL MATERIALS RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411509355.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, micro-nano particles are unevenly dispersed in metal substrates, expensive preparation costs and complex processes, making it difficult to achieve industrial production of high-performance metal-based composite materials.

Method used

Through the optimization of the preparation process, molten salt is used as a medium, and molten salt-micro-nano suspension is formed by ultrasonic stirring, and it is added to the metal melt, and the micro-nano particles are evenly distributed in the metal matrix by stirring and standing.

Benefits of technology

It realizes uniform dispersion of micro-nanoparticles in metal matrix, reduces preparation cost and process complexity, improves the comprehensive performance and stability of the material, and broadens its application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433259A_ABST
    Figure CN119433259A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal-based composite materials, and relates to a micro-nano particle reinforced metal-based composite material and a preparation method thereof. Comprising the following steps: mixing micro-nano reinforced particles and salt particles in proportion, heating to melt the salt particles, and ultrasonically stirring to obtain molten salt-micro-nano turbid liquid; smelting a metal matrix to obtain a metal melt, adding the molten salt-micro-nano suspension into the metal melt, stirring to obtain a mixture melt, and preserving heat; stopping stirring, allowing the mixture melt to stand, allowing the micro-nano reinforced particles to enter the metal melt from the molten salt to form an alloy melt, and keeping the temperature until the molten salt and the alloy melt are layered; and casting the alloy melt and the molten salt together, cooling, and stripping the salt body to obtain the micro-nano particle reinforced metal matrix composite material. According to the preparation method, the metal-based composite material with uniformly dispersed micro-nano particles is obtained by optimizing the preparation process, meanwhile, the preparation difficulty and the preparation cost are reduced, and a solution with application potential is provided for industrial production of the metal-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal matrix composite materials and relates to a micro-nano particle reinforced metal matrix composite material and a preparation method thereof. Background Art

[0002] In the field of research and development and production of metal matrix composites, the pursuit of high performance and low cost has always been the direction of unremitting efforts of scientific researchers. Metal matrix composites have shown broad application prospects in aerospace, automobile manufacturing, electronic packaging and other fields due to their excellent mechanical properties, good thermal stability and wear resistance. However, how to effectively and evenly disperse micro-nanoparticles into the metal matrix to achieve significant enhancement of material properties while maintaining the economy and feasibility of the preparation process is a major challenge currently facing this field.

[0003] In the preparation process of metal matrix composites, the addition method is a commonly used method. Its principle is to add solid fine particle reinforcements to the liquid metal matrix, and achieve uniform distribution of particles in the metal matrix through specific preparation processes and equipment. In this process, factors such as wettability, density difference, selection of preparation equipment, melting time and melting temperature all have a crucial impact on the quality of the final molded material. Wettability, that is, the ability of liquid to spread automatically on the solid surface, is one of the key factors that determine whether particles can be effectively dispersed. It involves a complex interaction between the surface tension of solid particles, the surface tension of liquids, and the solid-liquid interfacial tension. The equilibrium state of these forces directly affects the dispersion effect of particles in the metal melt.

[0004] However, there are many difficulties in the traditional addition method. On the one hand, the micro-nanoparticles added to the metal melt tend to increase the viscosity of the metal melt, which not only hinders the further dispersion of the particles that have not entered the melt, but also leads to a significant increase in preparation cost and time. In order to overcome this obstacle, the melting temperature sometimes has to be increased to reduce the melt viscosity, but this brings new problems, such as increased energy consumption, increased equipment wear, and possible impact on material properties. On the other hand, with the increase of melting time and melting temperature, the collision probability between micro-nanoparticles also increases, and the sintering phenomenon between particles becomes more and more serious, which not only damages the microstructure of the material, but also seriously affects the overall performance of metal matrix composites and the feasibility of industrial production.

[0005] In view of the above problems, the existing industrial production methods, such as 3D printing and in-situ endogenous method (powder metallurgy), can produce metal matrix composites with excellent performance, but their high preparation costs limit the wide application of these methods. Therefore, the development of a micro-nano particle reinforced metal matrix composite material and its preparation method that can effectively disperse micro-nano particles, control preparation costs, and ensure material performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of this, the present invention aims to provide a micro-nano particle reinforced metal matrix composite material and a preparation method thereof, by optimizing the preparation process, improving wettability and dispersibility, obtaining a metal matrix composite material with uniform dispersion of micro-nano particles, while reducing the preparation difficulty and preparation cost, and providing a solution with application potential for the industrial production of metal matrix composite materials.

[0007] In a first aspect, the present invention provides a method for preparing a micro-nano particle reinforced metal matrix composite material, comprising the following steps:

[0008] S1: mixing the micro-nano enhanced particles and the salt particles in proportion, heating the salt particles to melt them, and ultrasonically stirring the molten salt to obtain a molten salt-micro-nano suspension;

[0009] S2: melting the metal base to obtain a metal melt, adding the molten salt-micro-nano suspension into the metal melt, stirring to obtain a mixture melt and keeping the mixture warm;

[0010] S3: Stop stirring and let the mixture melt stand, the micro-nano enhanced particles enter the metal melt from the molten salt to form an alloy melt, and keep the temperature until the molten salt and the alloy melt are separated;

[0011] S4: Casting the alloy melt and molten salt together, and peeling off the salt body after cooling to obtain micro-nanoparticle reinforced metal matrix composites.

[0012] Optionally, the metal base is one or more of Al, Mg, Fe, Cu, Ti, Ni, Ag, Au and alloys thereof.

[0013] Optionally, the micro-nano reinforcing particles are one or more of TiC, TiB2, BN, ZrC, HfC, TaC, NbC, SiC, WC, WB, W, Al2O3, and Si3N4.

[0014] Optionally, the salt particles are one or more of NaCl, MgCl, RbCl, CsCl, KCl, Na2SO4, MgSO4, and K2SO4.

[0015] Optionally, in step S1, the volume ratio of the micro-nano enhanced particles to the salt particles is not less than 10%.

[0016] Optionally, the volume fraction of the micro-nano reinforced particles in the metal matrix is ​​designed to be 1 vol.% to 5 vol.%.

[0017] Optionally, in step S2, the metal is smelted in an inert gas.

[0018] Optionally, the temperature of heating the mixture of micro-nano reinforced particles and salt particles is the same as the temperature of melting the metal matrix. Optionally, in step S2, the melting temperature of the metal matrix is ​​100°C to 300°C higher than the melting point of the metal.

[0019] Optionally, in step S2, the stirring speed of the mixture melt is 500 to 1000 rpm, and the stirring time is 10 to 30 min.

[0020] Optionally, in step S3, the standing time of the mixture melt is 1 to 3 minutes.

[0021] In a second aspect, the present invention also provides a micro-nano particle reinforced metal matrix composite material prepared according to the above method.

[0022] In a third aspect, the present invention also provides an alloy product, which is mainly made of the above-mentioned micro-nano particle reinforced metal matrix composite material.

[0023] The beneficial effects of the present invention are:

[0024] The micro-nano particle reinforced metal matrix composite material and its preparation method of the present invention provide significant improvements and beneficial effects to the problems of uneven dispersion of micro-nano particles in the metal matrix, high preparation cost and complex process in the prior art. By using molten salt as a medium and utilizing its low melting point and low viscosity characteristics, the diffusion of substances and elements is promoted under low energy input. This innovation greatly optimizes the preparation process and reduces energy consumption.

[0025] Specifically, the present invention first adds micro-nano particles to molten salt and forms a molten salt-micro-nano suspension by ultrasound, stirring, etc., and then adds the suspension to the metal melt, and then forms fine droplets of dispersed distribution in the metal melt by vigorous stirring for 10 to 30 minutes at a rotation speed of 500-1000rpm. Compared with micro-nano particles and molten salt, the wettability between micro-nano particles and metal melt is smaller, so that the interfacial tension between metal melt and micro-nano particles is minimized, and the interfacial tension between molten salt and micro-nano particles pulls the interface front of molten salt and metal melt toward the molten salt, causing micro-nano particles to enter the metal melt. In addition, the molten salt phase is in the form of small spheres in the metal melt, and the size effect increases the interfacial tension between nanoparticles and molten salt, reduces the interfacial tension between molten salt and metal melt, promotes the diffusion of micro-nano particles, and enables them to be stably and evenly dispersed in the metal melt, thereby significantly improving the comprehensive performance and stability of the composite material.

[0026] Compared with the traditional preparation method, the present invention avoids the difficulty of dispersing micro-nano particles in the metal melt due to the increased viscosity, and the problem of particle sintering caused by long-term high-temperature smelting. At the same time, the difference in wettability between the molten salt and the metal melt allows the two to be quickly separated after the external force stops, which is convenient for the subsequent casting process, further simplifies the preparation process, and improves production efficiency.

[0027] In addition, the micro-nano particle reinforced metal matrix composite material prepared by the present invention has stable and uniform dispersion of the reinforcing phase inside the matrix, so that the material maintains the excellent properties of the metal matrix while significantly improving the hardness, wear resistance, corrosion resistance and other properties, broadening the application field of the material, and has extremely high industrial application value and market potential.

[0028] In summary, the preparation method of the present invention not only solves many problems in the prior art, but also provides a practical new approach for the industrial production of micro-nano particle reinforced metal matrix composite materials.

[0029] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0031] Figure 1A flow chart of a method for preparing a high-strength and high-conductivity copper-based composite material provided by the present invention;

[0032] Figure 2 This is the SEM image of the copper-based composite material prepared by powder metallurgy;

[0033] Figure 3 This is a SEM image of the copper-based composite material obtained in Example 1 of the present invention;

[0034] Figure 4 This is a SEM image of the copper-based composite material obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0035] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0036] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0037] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0038] In the field of metal-based composite materials, although their excellent performance makes them have broad application prospects in many industries, how to evenly disperse micro-nanoparticles into the metal matrix in an economical and efficient manner remains a technical challenge. In the traditional additive preparation process, the addition of particles will increase the melt viscosity, hinder further dispersion, increase the preparation cost and time, and at the same time, high-temperature and long-term smelting will cause particle sintering, which will damage the material properties. Although existing industrial production methods such as 3D printing and powder metallurgy can produce high-performance materials, their high costs limit their application.

[0039] Based on this, an embodiment of the present invention provides a method for preparing a high-strength and high-conductivity copper-based composite material. By optimizing the preparation process, a metal-based composite material with uniformly dispersed micro-nano particles is obtained, while reducing the preparation difficulty and preparation cost, providing a solution with application potential for the industrial production of metal-based composite materials.

[0040] like Figure 1 As shown, the preparation method comprises the following steps:

[0041] S1: mixing the micro-nano enhanced particles and the salt particles in proportion, heating the salt particles to melt them, and ultrasonically stirring the molten salt to obtain a molten salt-micro-nano suspension;

[0042] S2: melting the metal base to obtain a metal melt, adding the molten salt-micro-nano suspension into the metal melt, stirring to obtain a mixture melt and keeping the mixture warm;

[0043] S3: After stirring, the mixture melt is allowed to stand, and the micro-nano enhanced particles enter the metal melt from the molten salt to form an alloy melt, and the temperature is kept constant until the molten salt and the alloy melt are separated;

[0044] S4: Casting the alloy melt and molten salt together, and peeling off the salt body after cooling to obtain micro-nanoparticle reinforced metal matrix composites.

[0045] Specifically, in an embodiment of the present invention, the metal base is one or more of Al, Mg, Fe, Cu, Ti, Ni, Ag, Au and alloys thereof.

[0046] Specifically, in an embodiment of the present invention, the micro-nano reinforcing particles are one or more of TiC, TiB2, BN, ZrC, HfC, TaC, NbC, SiC, WC, WB, W, Al2O3, and Si3N4.

[0047] Specifically, in an embodiment of the present invention, the salt particles are one or more of NaCl, MgCl, RbCl, CsCl, KCl, Na2SO4, MgSO4, and K2SO4.

[0048] Specifically, in an embodiment of the present invention, the volume ratio of the micro-nano enhanced particles to the salt particles is not less than 10%.

[0049] Specifically, in an embodiment of the present invention, metal is smelted in an inert gas.

[0050] Specifically, in an embodiment of the present invention, the temperature at which the mixture of micro-nano reinforcement particles and salt particles is heated is the same as the temperature at which the metal matrix is ​​melted.

[0051] Specifically, in the embodiment of the present invention, the volume fraction of the micro-nano reinforced particles in the metal matrix is ​​designed to be 1 vol.% to 5 vol.%.

[0052] Specifically, in the embodiment of the present invention, the particle size of the micro-nano enhanced particles is below 200 nm.

[0053] Specifically, in an embodiment of the present invention, the melting temperature of the metal matrix is ​​100° C. to 300° C. higher than the melting point of the metal.

[0054] Specifically, in an embodiment of the present invention, in step S2, the mixture melt is continuously and vigorously stirred, the stirring speed is 500-1000 rpm, and the stirring time is 10-30 min.

[0055] Specifically, in the embodiment of the present invention, the standing time of the mixture melt is 1 to 3 minutes.

[0056] An embodiment of the present invention also provides a micro-nano particle reinforced metal matrix composite material prepared according to the above method.

[0057] An embodiment of the present invention further provides an alloy product, which is mainly made of the above-mentioned micro-nano particle reinforced metal matrix composite material.

[0058] Example 1

[0059] A method for preparing a micro-nano particle reinforced metal matrix composite material, wherein the metal matrix is ​​Al, the salt particles are NaCl-KCl mixed salt, and the micro-nano reinforced particles are TiC, specifically comprising the following steps:

[0060] (1) Weigh 100 g of NaCl-KCl composite salt particles and 2 g of TiC particles with a particle size of 150 nm, place the two in a drying oven at 150° C. for 3 h, and then mix them by acoustic resonance after drying;

[0061] (2) heating the NaCl-KCl-TiC composite powder at a high temperature of 750° C. to melt the composite salt into a NaCl-KCl molten salt, stirring the NaCl-KCl-TiC mixed melt at a speed of 750 rpm for 10 min to form a NaCl-KCl-TiC suspension and keeping the suspension at 750° C.;

[0062] (3) 100 g of Al pellets were melted at 750 °C to form an Al melt, and the NaCl-KCl-TiC suspension was added to the Al melt. The stirring device was turned on at a speed of 750 rpm for 10 min. The entire melting process was carried out under the protection of an inert gas.

[0063] (4) Stop stirring and let stand for 3 min to allow the NaCl-KCl molten salt and the TiC-Al alloy melt to separate into layers;

[0064] (5) The TiC-Al alloy melt and the NaCl-KCl salt melt are cast together and cooled, and the titanium carbide reinforced aluminum matrix composite material is obtained after the salt body is peeled off.

[0065] The scanning electron microscope observation results of the titanium carbide reinforced aluminum matrix composite material prepared in this embodiment are as follows: Figure 3 As shown, Figure 2 This is a SEM image of a copper-based composite material prepared by powder metallurgy. It can be seen that, compared with the powder metallurgy method, the titanium carbide particles prepared in this embodiment are evenly distributed on the Al surface without obvious agglomeration.

[0066] Example 2

[0067] A preparation method of a micro-nano particle reinforced metal matrix composite material, wherein the metal matrix is ​​Cu, the salt particles are NaCl-KCl mixed salt, and the micro-nano reinforced particles are WC. The whole process is carried out under the protection of an inert gas, and specifically comprises the following steps:

[0068] (1) Weigh 100 g of NaCl-KCl composite salt particles with a mass ratio of 1:1 and 1.7 g of WC particles with a particle size of 150 nm, place the two in a drying oven at 150°C for 3 h, and mix them by acoustic resonance after drying;

[0069] (2) heating the NaCl-KCl-WC composite powder at a high temperature of 1250° C. to melt the composite salt into a NaCl-KCl molten salt, stirring the NaCl-KCl-WC mixed melt at a speed of 750 rpm for 10 min to form a NaCl-KCl-WC suspension and keeping the mixture at 1250° C.;

[0070] (3) Weigh 100 g of copper particles and smelt them at 1250°C to form a Cu melt. Add the NaCl-KCl-WC suspension into the Cu melt, turn on the stirring device, the speed is 750 rpm, the stirring time is 10 min, and the entire smelting process is carried out under the protection of inert gas;

[0071] (4) Stop stirring and let stand for 3 min to allow the NaCl-KCl molten salt and the WC-Cu alloy melt to separate into layers;

[0072] (5) The WC-Cu alloy melt and the NaCl-KCl salt melt are cast together and cooled, and the tungsten carbide reinforced copper matrix composite material is obtained after the salt body is peeled off.

[0073] The scanning electron microscope observation results of the tungsten carbide reinforced copper matrix composite material prepared in this embodiment are as follows: Figure 4 As shown, Figure 2 This is a SEM image of a copper-based composite material prepared by powder metallurgy. It can be seen that compared with the powder metallurgy method, the tungsten carbide particles prepared in this embodiment are evenly distributed on the Cu surface without obvious agglomeration.

[0074] Pure copper and pure aluminum were used as comparative samples, and the composite material prepared in Example 1 and the composite material prepared in Example 2 were used as experimental samples. The electrical conductivity, hardness and tensile strength thereof were tested respectively. The results are shown in Table 1.

[0075] Table 1

[0076] Material Type Electrical conductivity (IACS%) Hardness(Hv) Tensile strength(MPa) Pure Copper 100 60 200 Pure aluminum 60 30 100 Example 1 40 70 300 Example 2 82 130 450

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a micro-nano particle reinforced metal matrix composite material, characterized in that: The following steps are involved: S1: mixing micro-nano enhanced particles and salt particles in proportion, heating to melt the salt particles, and ultrasonically stirring the molten salt to obtain a molten salt-micro-nano suspension; S2: melting a metal base to obtain a metal melt, adding the molten salt-micro-nano suspension to the metal melt, stirring to obtain a mixture melt and keeping the mixture warm; S3: stopping stirring and leaving the mixture melt still, the micro-nano enhanced particles enter the metal melt from the molten salt to form an alloy melt, and keeping the temperature continuously until the molten salt and the alloy melt are separated into layers; S4: Casting the alloy melt and molten salt together, and peeling off the salt body after cooling to obtain micro-nanoparticle reinforced metal matrix composites.

2. The preparation method according to claim 1, characterized in that: The metal matrix is ​​one or more of Al, Mg, Fe, Cu, Ti, Ni, Ag, Au and alloys thereof.

3. The preparation method according to claim 1, characterized in that: The micro-nano enhanced particles are one or more of TiC, TiB2, BN, ZrC, HfC, TaC, NbC, SiC, WC, WB, W, Al2O3, and Si3N4.

4. The preparation method according to claim 1, characterized in that: The salt particles are one or more of NaCl, MgCl, RbCl, CsCl, KCl, Na2SO4, MgSO4, and K2SO4.

5. The preparation method according to claim 1, characterized in that: In step S1, the volume ratio of the micro-nano enhanced particles to the salt particles is not less than 10%.

6. The preparation method according to claim 1, characterized in that: The designed volume fraction of the micro-nano reinforced particles in the metal matrix is ​​1 vol.% to 5 vol.%.

7. The preparation method according to claim 1, characterized in that: In step S2, metal is smelted in an inert gas.

8. The preparation method according to claim 1, characterized in that: The temperature at which the mixture of the micro-nano reinforced particles and the salt particles is heated is the same as the temperature at which the metal matrix is ​​melted.

9. The preparation method according to claim 1, characterized in that: In step S2, the melting temperature of the metal base is 100°C to 300°C higher than the melting point of the metal.

10. The preparation method according to claim 1, characterized in that: In step S2, the mixture melt is stirred at a stirring speed of 500 to 1000 rpm and a stirring time of 10 to 30 min.

11. The preparation method according to claim 1, characterized in that: In step S3, the mixture melt is allowed to stand for 1 to 3 minutes.

12. A micro-nano particle reinforced metal matrix composite material prepared by the method according to any one of claims 1 to 11.

13. An alloy product, characterized in that: The alloy product is mainly made of the micro-nano particle reinforced metal matrix composite material described in claim 12.